Visual stylistics and Literary Flavor in the Anthology Flock of Birds Above the Temple by Chokchai Bundit - ทิพนา, สันติ (Journal of Roi Et Rajabhat University, 2023)
This research paper aimed to analyze the visual stylistics and literary flavor in poetry of Chokchai Bundit anthology of Birds Above the Temple, which won the outstanding poetry award in the Outstanding Book Contest in 2021, the Office of the Basic Education Commission, Ministry of Education, total 63 chapters. This research relied on theories, rhetoric, imagery and flavors of Sanskrit literature and flavors of Thai literature to be synthesized as criteria for study. The results showed that there are 6 types of rhetoric that appear: 1) metaphor, 2) metaphor, 3) apocalypse, 4) phonetic, 5) personality, and 6) noun. The 10 flavors of literature are: 1) Shantaras, such as forgiveness and peace, 2) Saringkaras or Naripramot, such as a mother's love for her child, remembering teachers, 3) Anger or anger towards animals and people, 4) Kindness or sallapankpisai, such as disappointment in love, suffering, 5) passion fruit, such as viewing flowers and nature, 6) Bhayankorns, such as fear or worry about events, 7) heroism such as perseverance and courage, 8) Atphuts, such as surprise and modernity, 9) Pepatsorn, such as feeling bored of poor work and society, and 10) Finding flavors such as humor. The rhetorical analysis of literary imagery in Chokchai Bundit poetry entitled Flock of Birds Nua Viharn is just an analysis according to aesthetic concepts to see the beauty of literature.